Harmonisasi Regulasi : Kunci Stabilitas Hukum Dalam Investasi dan Pembangunan Ekonomi Pasca Pemberlakuan UU Cipta Kerja - Alfiqri, Khadafi; Khadafi; Indra Rathana; Dewi Indriani Jusuf; Elli Ruslina (Siyasah, 2025)
Legal politics is an important element when creating a number of policies and regulations that will be enforced in society. Economic development is a process that is carried out on an ongoing basis to achieve prosperity and progress for the nation. In an effort to encourage economic growth and increase global competitiveness, the Indonesian government introduced the Job Creation Law (UU Job Creation). This research method is normative legal research, with data sourced from library research. This research can provide benefits in the form of input, especially in economic development and investment. The Job Creation Law also increases transparency in the licensing process by requiring all licensing information and requirements to be openly available and accessible online. However, in investment policy after the Job Creation Law, there is still legal uncertainty and the potential for overlapping regulations at the central and regional levels. The government needs to increase harmonization and synchronization between regional regulations and higher laws and regulations. Coordination is very important as an effort to harmonize regulations, because licensing issues are not only at the central and regional levels but cross-sectoral at a national level..